Nonclassicality generated by photon annihilation-then-creation and creation-then-annihilation operations - Ooi, Chong Heng Raymond; Lee, H.W.; Lee, S.Y.; Park, J.; Ji, S.W. (Optical Society of America, 2009)
We examine nonclassical properties of the field states generated by applying a photon annihilation-then-creation operation (AC) and a creation-then-annihilation operation (CA) to the thermal and coherent states. Effects of repeated applications of AC and of CA are also studied. We also discuss experimental schemes to realize AC and CA with a cavity system using atom-field interactions. (C) 2009 Optical Society of America